2020
DOI: 10.3390/jcm9113771
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Active Therapy-Based Training to Improve the Balance in Patients with Fibromyalgia: A Systematic Review with Meta-Analysis

Abstract: Balance impairment is a frequent disorder in patients with fibromyalgia (FMS), increasing the risk of falls and decreasing physical function and quality of life. In recent years, the use of active therapy-based training (ATBT) has increased, with the aim of improving balance in women with FMS. Our study aimed to assess the effect of ATBT to improve different balance outcomes in subjects with FMS. A systematic review with meta-analysis was carried out. We searched PubMed Medline, SCOPUS, Web of Science, CINAHL,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 58 publications
2
6
0
Order By: Relevance
“…Our results suggested that VRBT improves dynamic balance in subjects with FMS. VRBT is an active therapy that requires engaging in physical activities during the sessions, and the findings obtained were similar to those in different reviews that assessed the effects of physical exercise or Tai Chi to increase the balance in FMS women [25,85]. According to Villafaina, S. et al, 2019 [63], VRBT produces changes in different brain areas and increases the grey matter and EEG signals in the frontal, parietal, temporal and occipital lobes, some of which are responsible for integrating the balance information needed to respond to a destabilizing stimulus or Earth's gravitational force.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Our results suggested that VRBT improves dynamic balance in subjects with FMS. VRBT is an active therapy that requires engaging in physical activities during the sessions, and the findings obtained were similar to those in different reviews that assessed the effects of physical exercise or Tai Chi to increase the balance in FMS women [25,85]. According to Villafaina, S. et al, 2019 [63], VRBT produces changes in different brain areas and increases the grey matter and EEG signals in the frontal, parietal, temporal and occipital lobes, some of which are responsible for integrating the balance information needed to respond to a destabilizing stimulus or Earth's gravitational force.…”
Section: Discussionsupporting
confidence: 75%
“…In addition to pharmacotherapy, conservative non-pharmacological interventions based on physiotherapy, conventional therapy (CT), or physical exercise are another modality in the treatment of FMS [24]. Recent studies have highlighted active physical training as an effective therapy to improve balance [25], pain [26], muscle fatigue [27], anxiety [28] and QoL [29], among others, in patients with FMS. However, with the aim to get an increasing in the effect of CT, new technologies have been used.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have focused on the effects of acupuncture on fatigue, sleep disturbance, anxiety and depression. 12 , 13 With the increasing number of studies on balance disorders in fibromyalgia patients in recent years, 2 , 34 researchers in this field have also begun to pay attention to the effects of acupuncture on balance disorders in fibromyalgia. Research has shown that acupuncture improves dynamic equilibrium and postural control in women with fibromyalgia, with effects sustained for 5 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our findings have important implications for clinical practice as balance disorders detected in patients with FMS correlate with the impact of the disease. A review with meta-analysis recently found that the balance disorder presented by patients with FMS can be treated with Training Based on Active Therapy [ 67 ]. However, the effect detected in this review is moderate or low and occurs in the short term.…”
Section: Discussionmentioning
confidence: 99%